Distributed, scalable routing based on link-state vectors. - Behrens, Jochen (Computer communication review.)
A new family of routing algorithms for the distributed maintenance of routing information in large networks and internets is introduced. This family is called link vector algorithms (LVA), and is based on the selective diffusion of link-state information based on the distributed computation of preferred paths, rather than on the flooding of complete link-state information based on the distributed computation of preferred paths, rather than on the flooding of complete link-state information to all routers. According to LVA, each router maintains a subset of the topology that corresponds to the links used by its neighbor routers in their preferred paths to known destinations. Based on that subset of topology information, the router derives its own preferred paths and communicates the corresponding link-state information to its neighbors. An update message contains a vector of updates; each such update specifies a link and its parameters. LVAs can be used for different types of routing. The correctness of LVA is verified for arbitrary types of routing when correct and deterministic algorithms are used to select preferred paths at each router. LVA is shown to have smaller complexity than link-state and distance-vector algorithms, and to have better average performance than the ideal topology-broadcast algorithm and the distributed Bellman-Ford algorithm.